2016
DOI: 10.1017/ice.2016.269
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Prescribing: Examining the Frequency of Antimicrobial Prescriptions Without a Patient Visit

Abstract: Objective To investigate the scale of antimicrobial prescribing without a corresponding visit, and to compare the attributes of patients who received antimicrobials with a corresponding visit to those who did not have a visit. Design Retrospective cohort Methods We followed 185,010 Medicare patients for one year after an acute myocardial infarction. For each antimicrobial prescribed, we determined if the patient had an inpatient, outpatient or provider claim in the 7 days prior to the antimicrobial prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
3
10
1
Order By: Relevance
“…Second, approximately one-third of antibiotic prescriptions were generated by non-face-to-face encounters, which typically lack an associated code. Our rate of such "phantom" prescribing was greater than the ϳ15% rate estimated in a study of Medicare patients with recent myocardial infarction (19), suggesting that it may be fruitful for stewardship programs to address such practices. To ascertain a true estimate of antibiotic utilization, centers may find greater benefit in reviewing lists of all antibiotics prescribed, as was done here, rather than focusing exclusively on infectionassociated diagnosis codes.…”
Section: Discussioncontrasting
confidence: 60%
“…Second, approximately one-third of antibiotic prescriptions were generated by non-face-to-face encounters, which typically lack an associated code. Our rate of such "phantom" prescribing was greater than the ϳ15% rate estimated in a study of Medicare patients with recent myocardial infarction (19), suggesting that it may be fruitful for stewardship programs to address such practices. To ascertain a true estimate of antibiotic utilization, centers may find greater benefit in reviewing lists of all antibiotics prescribed, as was done here, rather than focusing exclusively on infectionassociated diagnosis codes.…”
Section: Discussioncontrasting
confidence: 60%
“…27 Second, pharmacy claims data do not contain information about the condition the drug is intended to treat, so our matching of encounters and prescriptions may have measurement bias or be affected by trends in coding practice. 28,29 In addition, we were not able to classify approximately 18% of antibiotic claims as appropriate or inappropriate because they had no associated diagnoses, similar to a previous study 30 that found that 15% of Medicare antibiotic claims had no associated encounter. Third, the 5-year period of our study prevents assessment of…”
Section: Discussionsupporting
confidence: 63%
“…This will occur even when the distribution of the data is approximately bell-shaped. In another example of accurate estimation leading to a small p-value, Riedle et al (2017) show that the odds of a patient over 85 years of age receiving an antimicrobial prescription without a corresponding visit to a clinician is only 1.055 (95% CI : (1.023, 1.088)) times the odds for a patient under 85, yet the p-value is 0.0007. Because this odds ratio is accurately estimated, then a fairly modest effect is able to reach a high level of statistical significance.…”
Section: P-value Controversiesmentioning
confidence: 99%
“…Our second application seeks to determine whether white patients who are prescribed antimicrobials are more likely to receive the prescription without a corresponding physician visit. This application is based on results from Riedle et al (2017). Antimicrobial resistance is a major public health concern.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation